Arc plasma synthesis of IV-V groups transition metals high-entropy carbides cubic phases - Gumovskaya A. A. Arina Andreevna; Pak A. Ya. Aleksandr Yakovlevich; Bolatova Zh. S. Zhanar Sanatovna; Povalyaev P. V. Pavel Vadimovich; Gerasimov R. D. Roman Dmitrievich (2022, 2022)
Title screen